Formulasi Pengaturan ‘Pengakuan Bersalah’ Dalam Rancangan Kitab Undang-Undang Hukum Acara Pidana (Studi Perbandingan Konsep Plea Bargaining Di Amerika Serikat Dan Inggris) - Mayo Ramza Pratama; Ayu Izza Elvany (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This research aims to compare the special track regulations in the Indonesian Draft Criminal Procedure Code (RKUHAP) with the concept of Plea Bargaining in the United States and Plea Negotiations in the United Kingdom. Additionally, this study also aims to identify the ideal concepts of Plea Bargaining and Plea Negotiations to be applied to the special way system in Indonesia. The research method used is normative juridical with statutory, comparative, and conceptual approaches. The results show that although there are significant differences in implementation, application requirements, procedures, the authority of law enforcement officials, defendant's rights, and the outcomes of agreements among the three systems, there is a common goal of achieving efficiency in the judicial process and reducing the judicial burden. The special track concept in the RKUHAP, inspired by practices in the United States and the United Kingdom, is expected to expedite the resolution of criminal cases for defendants who admit their guilt. However, its regulation in the RKUHAP is considered to have shortcomings and lacks detail, particularly regarding the mechanism of confession, case referral, forms of agreement, the role of law enforcement officials, criminal sanctions, and procedures for retracting confessions. This study recommends that the Government and the House of Representatives conduct an in-depth review of the implementation of plea bargaining mechanisms and their supporting regulatory infrastructure, taking into account the experiences of the United States and the United Kingdom, as well as the principles of justice, transparency, and strict oversight.